Modeling Long-Term Photometric Data of Trans-Neptunian Objects and Centaurs - Fernández-Valenzuela, Estela (Frontiers in Astronomy and Space Sciences, 2022)
Trans-Neptunian objects and Centaurs are small Solar System bodies that reside in the outer parts of the Solar System. These objects present photometric behaviors that are influenced due to a change in their aspect angle. Using absolute photometric measurements and rotational light-curves at different locations on their orbits allows to model their photometric behavior and obtain physical properties such as pole orientation, shape, density, and even detecting different peculiarities as departure from hydrostatic equilibrium or rings. This work presents how these models are performed to extract different physical properties. A summary of the objects for which their long-term photometric behavior has been modeled is also given.